Encapsulation Properties and Digestibility of Encapsulated Aloe vera Bioactive Polysaccharides - Auppasuk, Phikunthong; Polklang, Wipaporn; Lueachan, Rachata; Ploypetchara, Thongkorn; Budseekoad, Siriporn; Siricoon, Sinee; Sumsakul, Wiriyaporn; Auranwiwat, Chiramet; Sorndech, Waraporn (Thai Journal of Science and Technology, 2024)
Aloe vera is the famous medicinal plant that has been used in the treatment of many diseases. New findings showed that Aloe vera extract can stimulate the osteoblast differentiation in human fetal osteoblast cells which can potentially be used as functional ingredient for increasing bone mass. This study aimed to contribute to this growing area of functional ingredient related to non-communicable diseases (NCDs) research by exploring the effect of encapsulation wall-materials on encapsulation properties and digestibility of Aloe vera extracts. Aloe vera extract (2.0% wv-1) were encapsulated with 7.5% (wv-1) maltodextrin (MD), 7.5% (wv-1) gum arabic (GA) and their mixtures (5% (wv-1) MD + 2.5% (wv-1) GA and 2.5% (wv-1) MD + 5% (wv-1) GA) at 50 oC for 16 h using hot air dryer. The results of the encapsulation efficiency (EE) showed that an increase in GA content could increase encapsulation efficiency as compared to MD-only wall-material. GA-only wall-material provided the highest EE (94.96%) while the MD only provided the lowest EE (68.71%). The appearance of encapsulated extract displayed an increase in yellow color when increasing GA content which was corresponded to an increase in positive b* value. The encapsulated microstructure of all samples showed smooth surface, angular and fragmentation structures indicated a break down in the encapsulated structure after drying. There was a significant positive correlation between an increase in GA content and antioxidant activity. Moreover, an increase in GA content as wall-materials showed restricted reducing sugar release following hydrolysis by porcine pancreatic α-amylase, pepsin, pancreatin and glucoamylase. Hence, GA could extend a release of bioactive compounds during digestion. These data led to an enhanced understanding of encapsulated bioactive compounds delivery and how encapsulation wall materials and Aloe vera extract affected the encapsulated physicochemical properties and digestibility. Further research should be undertaken to explore how bioactive compounds and wall-materials interaction target delivery and control bioactive compounds release which will be a pivotal role in the future of personalized diet.